Reward System Design and Group Creativity: An Experimental Investigation - Chen, Clara Xiaoling; Williamson, Michael G.; Zhou, Flora H. (The Accounting Review, 2012)
ABSTRACT In an environment where three-person groups develop a creative solution to an important problem, we examine whether the efficacy of either individual- or group-based creativity-contingent incentives depends on whether they take the piece-rate or tournament form. We predict and find that group (intergroup) tournament pay increases group cohesion and collaborative efforts, which ultimately lead to a more creative group solution, relative to group piece-rate pay. While individual (intragroup) tournament pay increases individual efforts, we find that it does not enhance the creativity of group solutions relative to individual piece-rate pay. Our results advance the burgeoning management accounting literature on creativity-contingent incentives by demonstrating that reward systems are more likely to promote group creativity through collaborative efforts rather than independent individual efforts. We also provide important insights into when and why tournament pay can boost group creativity in organizations. In doing so, we contribute to a better understanding of observations from practice suggesting that organizations valuing creativity often induce intergroup competition. Data Availability: The experimental data are available upon request.